Study of Women's Leadership Roles and Its Effect on Middle-Countries Economy - Fathia, Syaharani Noer; Nur Susilowati, Retno Yuni; Majidah, Rona; Octary, Ayu Dwiny; Rohman, Fatkhur (CV. Era Digital Nusantara, 2025)
The Sustainable Development Goals (SDGs) represent the United Nations' agenda for sustainable development, encompassing 17 objectives, with Goal 5 focusing on